2011
DOI: 10.3892/mmr.2011.664
|View full text |Cite
|
Sign up to set email alerts
|

Expression of paxillin and FAK mRNA and the related clinical significance in esophageal carcinoma

Abstract: Abstract. The objective of the present study was to investigate the expression of paxillin and focal adhesion kinase (FAK) mRNA in esophageal carcinoma tissues, and their relationship with clinicopathological parameters, as well as to analyze the correlation of paxillin and FAK mRNA levels in esophageal carcinoma. By using reverse transcription polymerase chain reaction (RT-PCR), the mRNA expression levels of paxillin and FAK were detected in 121 samples of esophageal carcinoma, 43 samples of atypical hyperpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Our results demonstrate significantly greater expression of fascin-1, ezrin and paxillin in LSCC than ANM tissues, which agrees with observations in ESCC [15], [34], gastric cancer [42], and NSCLC [31], [37]. Fascin-1, ezrin or paxillin might promote the malignant progression of LSCC; therefore, we investigated whether fascin-1, ezrin or paxillin levels could be potential molecular markers to determine LSCC prognosis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results demonstrate significantly greater expression of fascin-1, ezrin and paxillin in LSCC than ANM tissues, which agrees with observations in ESCC [15], [34], gastric cancer [42], and NSCLC [31], [37]. Fascin-1, ezrin or paxillin might promote the malignant progression of LSCC; therefore, we investigated whether fascin-1, ezrin or paxillin levels could be potential molecular markers to determine LSCC prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…It has been linked to many malignancies [33], [34], [35], [36], [37], [38], [39] except LSCC. Paxillin was highly expressed in 69.0% of our cases, which was similar to the proportion found for HCC [36] and urothelial bladder tumor [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cai et al (21) found that paxillin mRNA expression levels were significantly correlated with the differentiation degree, depth of invasion and lymph node metastasis of esophageal carcinoma. A previous study indicated that paxillin expression was correlated with distant metastasis and clinical stage of salivary adenoid cystic carcinoma (22).…”
Section: Discussionmentioning
confidence: 99%
“…FAK overexpression has been associated with breast cancer lung metastasis (37,38), and FAK inhibitors have been introduced in novel therapeutic strategies (20,(39)(40)(41). An association between FAK overexpression and lymphatic metastasis has been identified in non-small-cell lung, oral squamous cell, esophageal, gastric, tongue, laryngeal and endometrial cancer by retrospective analysis of clinical samples (42)(43)(44)(45)(46)(47)(48)(49). Upregulation of FAK in the SKOV-3/LN403 cell line and clinical pathological specimens suggests that it may contribute to the high lymphatic metastaticity of the SKOV-3/LN403 cell line.…”
Section: Discussionmentioning
confidence: 99%